Prevalence and prognosis of molecularly defined familial hypercholesterolemia in patients with acute coronary syndrome - Wang, Cheng; Yu, Puliang; Hu, Lizhi; Liang, Minglu; Mao, Yi; Zeng, Qiutang; Wang, Xiang; Huang, Kai; Yan, Jin; Xie, Li; Zhang, Fengxiao; Zhu, Feng (Frontiers in Cardiovascular Medicine, 2022)
Background: Familial hypercholesterolemia (FH) can cause the elevation of serum low-density lipoprotein cholesterol (LDL-C), which could promote the progress of acute coronary syndrome (ACS), but the effect of FH on the prognosis of ACS remains unclear. Methods: In this prospective cohort study, 223 ACS patients with LDL-C ≥ 135.3 mg/dL (3.5 mmol/L) were enrolled and screened for FH on a multiple-gene panel for FH. The diagnosis of FH is defined as carrying pathogenic or likely pathogenic variants according to the ACMG/AMP criteria. The clinical features of FH and the relationship of FH to the average 16.6 months risk of cardiovascular events (CVEs) were assessed. Results: The prevalence of molecularly defined FH in the enrolled patients was 26.9%, and coronary artery lesions in FH patients were more severe than those in non-FH patients (Gensini score 66.0 vs. 28.0, respectively; P<0.001). After lipid lowering, patients with FH still had a signiﬁcantly higher LDL-C level at their last visit (73.5±25.9mg/dl vs. 84.7±37.1mg/dl; P=0.013) compared with those without. We also found that FH patients increased the incidence of CVEs in ACS patients (hazards ratio: 3.058; 95% confidence interval: 1.585-5.900; log-rank P<0.001). Conclusions: FH is associated with the increased risk of CVEs in ACS, is an independent risk factor of ACS. The study also highlights the importance of genetic testing of FH-related gene mutations in ACS patients.